DEVELOPMENT OF A PROBLEM BASED LEARNING ORIENTED PHYSICS E-MODULE TO IMPROVE THE SCIENTIFIC LITERACY OF HIGH SCHOOL STUDENTS - Pertiwi, Bella; Purwanto, Andik; Setiawan, Iwan (Universitas Tanjungpura, 2024)
This study aims to: 1) develop a problem-based learning-oriented physics e-module to improve the science literacy of high school students, 2) determine the feasibility of the e-module, 3) determine students' perceptions of the e-module. The method used in this study is Research and Development (RD) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. However, this research was carried out limited to only the Development stage because limited research time, research costs, and adjustments to the needs of development research. The research instruments used are: 1) validation sheets of material experts, media experts, and learning design experts to find out the feasibility of the e-module being developed, 2) Student perception questionnaire to find out students' responses to the developed e-module. The results of this study showed that the results of the validation test received an average assessment of all aspects for material experts of 97.47% with very decent categories, media experts of 92.61% with very decent categories, and learning design experts of 96.52% with very decent categories and for student perception results obtained an average of all aspects of 94.23% with excellent categories. Based on the results of expert validation tests and the results of students' perceptions, it can be concluded that the products developed are decent for use as a medium for learning physics in schools.